LEGAL PROTECTION QUICK RESPONSE CODE AS A PAYMENT SYSTEM - Normalita Destyarini; Falah Al Ghozali; Muhamad Rois (LPPM Universitas Duta Bangsa Surakarta, 2022)
Technology in the payment system brings convenience to its users and as an effort to improve the economy, the use of QR Code technology. Indonesia has a standardized standard in terms of using the QR Code, namely by using QRIS (Quick Response Code Indonesian Standard) issued by payment service providers as stipulated in the Regulation of the Members of the Board of Governors of Bank Indonesia Number 23/6/PBI/2021 concerning Payment Service Providers. There are risks that may arise, namely the occurrence of QRIS transaction fraud. Sanctions for Payment Service Providers as in the Regulation of Members of the Board of Governors of Bank Indonesia Number 23/6 / PBI / 2021 concerning Payment Service Providers in the form of administrative sanctions to termination of business activities further Law Number 13 of 2011 concerning Fund Transfers Article 79 to Article 86 by providing criminal provisions for perpetrators of fund transfers that do not have a license.